(untitled) - MAHFUDHOTIN, NURUL (RETAIN : Journal of Research in English Language Teaching, 2014)
The Implementation of Four-Square Writing Technique in Teaching Writing Narrative Writing of Short Story to Tenth Grader of Senior High School Nurul Mahfudhotin English Education Faculty of Languages and Arts State University of Surabaya nu.shine46@gmail.com Name : Nurul Mahfudhotin NIM : 102084040 Study Program : S-1 Pendidikan Bahasa Inggris Faculty : Language and Arts Institution : Surabaya State University Advisor : Dr. Oikurema Purwati, M.Appl. Years : 2014 Penelitian ini bertujuan untuk mendeskripsikan penerapan four-square writing technique dalam pengajaran penulisan naratif dalam bentuk cerita pendek kepada siswa kelas X Sekolah Menengah Atas. Penelitian ini menyusun beberapa pertanyan : (1) bagaimana guru menerapkan four-square writing technique dalam pengajaran penulisan naratif dalam bentuk cerita pendek? dan (2) bagaimana tugas siswa setelah penerapan four-square writing technique? Penelitian ini telah membuktikan bahwa four-square writing technique dapat membantu siswa dalam menyusun sebuah teks naratif. Penelitian menunjukkan keuntungan dari four-square writing technique terhadap komposisi tulisan siswa. Komposisi siswa menunjukkan hasil yang baik setelah dianalisa menggunakan ESL Composition Measurement oleh Jacob. Penelitian ini menyimpulkan bahwa four-square writing technique adalah teknik yang berguna untuk membantu siswa menyusun sebuah teks naratif. Kata Kunci: menulis, teks naratif, cerita pendek, teknik four-square writing This study is designed to describe the implementation of four-square writing technique in teaching narrative writing of short story to tenth grader of senior high school. This study composes some questions: (1) how does the teacher implement four-square writing technique in teaching narrative writing of short story? And (2) how is the students’ task after the implementation of Four Square Writing Technique? This study has proved that the Four Square Writing Technique can help the students in composing a narrative text. The study shows the benefits of the Four Square Writing Technique towards the students writing composition. The students’ composition showed good result after being analyzed by using by Jacob. The study concludes that Four Square Writing Technique is a useful technique to help the students compose a narrative text. Keywords: writing, narrative text, short story, four-square writing technique INTRODUCTION Writing as one of productive skill is also used in written communication. According to J.D Angelo (1989), writing is a form of thinking. Writing is an activity of expressing someone’s idea, feeling or thinking in written form. When someone tries to write something, the writing will show everything on their minds. One of text genres which learnt by the students of senior high school is Narrative text. Warringer (1986) states that Narrative is a kind of discourse that answer the question “what happened”. Narrative tells something happened in past such as legend, myth, fable, fairytale and personal experience which has problem and resolution in it. Some students find it is difficult to express their idea in written form, especially in English as it is not their native language. Writing is difficult not only for second or foreign language learners but also for native language learners (Nunan, 1991). One of text genres which learnt by the students of senior high school is Narrative text. Warringer (1986) states that Narrative is a kind of discourse that answer the question “what happened”.Susanti (2005) argues that the students are still confused about English rules which cause them hard to form Narrative composition. In this study, the writer wants to promote another solution that is Four-Square Technique. Four-Square Technique is a Technique to help students organize their idea by filling their ideas into Four-Square shape with some clues to form their writing. This Technique is actually quite similar to mind mapping, since both of them are used to generate ideas. However, they have some differences. First, in Four-Square Technique, students are asked to put their ideas into four-square shape, so they can only have four ideas to be explain. While in mind mapping, students can put their ideas in any shape and it is not limited. Another difference is that in mind mapping, the students have to put some words to form sentences, but in Four Square Writing Technique the students have to put a idea for each paragraph. Gould (1999) describes that Four-Square Technique is the way to helps the students interested and motivated in easy organization in every square they have. There were some studies conducted in applying Four-Square Writing Technique to help the students develop their writing skills. Two of them were done by Fatimah (2010) who conducted research on the implementation of Four-Square Writing Technique in writing recount text and Darmawan (2011) who also conducted research on the implementation of Four-Square Writing Technique in writing descriptive text. From the background of study above, the writer comes up with research questions: (1) how does the teacher implement Four Square Writing Technique in teaching Narrative Writing of Short Story? and (2) how is the students’ task after the implementation of Four Square Writing Technique? METHOD This study was conducted by using descriptive qualitative design. In this research, there was no control of treatment as in experimental research. Ary et. al. (2010) states that qualitative research is a research that investigates the quality of relationships, activities, situations, and materials. On the other hand, Huda (1999) defines qualitative research is usually associated with the method of analyzing data and writing the research report. Qualitative research studies behavior as it occurs naturally in a classroom (Ary et. al., 2010). The researcher conducted observation two times. The researcher tried to describe her study by using words in explaining the data according to the objectives of this study. In this study, the researcher focused on the teaching and learning process, especially on the students’ Narrative writing of short story. This study is held in SMA Muhammadiyah 2 Surabaya. The subjects of this study were the students of X MIIA 1 SMA Muhammadiyah 2 Surabaya, which consisted of 25 students. Unfortunately, three students were absent when the writer conducted the research. The data of this study are the result of the observation and the result of students’ tasks. The result of the observation includes the teachers’ activities during the teaching and learning process, while the result of the students’ tasks refers to the narrative composition that the students write. After getting all of the data needed, the researcher analyzes the data qualitatively in descriptive way using words and sentences. The data are taken during the teaching and learning process in the classroom. The data are analyzed based on the result of observation and the students’ tasks. The result of observation analysis is based on the teaching and learning activities during the implementation of four-square writing technique in teaching narrative writing. While the students’ tasks are used to analyze the students’ narrative composition regarding on the organization, content, vocabulary, language used and mechanic using ESL Composition Measurement by Jacob (1981). The result of students’ tasks analysis describes their ability in composing narrative text. IMPLEMENTATION OF FOUR-SQUARE WRITING TECHNIQUE The first meeting was conducted on Thursday, 10 April 2014 at 07.40 a.m. The class began 10 minutes late because the previous teacher had not ended her explanation when the English teacher came. While waiting for the previous teacher to finish her explanation, the English teacher rechecked her preparation for teaching. When the teacher entered the classroom, the students were sitting on their chair. They were separated into two group, male students and female students. The students were getting interested in the material, which is narrative text. They interacted actively, discussing the kinds of narrative text they had already learned.The students were able to mention some of narrative kinds. They also mentioned its generic structure and langguage feature. The second meeting was held on Thursday, 10th April 2014 at 7 th and 8 th periods which were started from 12.30 until 02.00 p.m. The class was started right after them having their break time for praying and having lunch. When the teacher entered the classroom, the students were not ready for teaching and learning process. Some students were talking to their friends; some were eating snacks, some of the students in the back row also still playing with their gadgets. The teacher started the lesson right after the students preparing themselves. The class began at 12.35. The teacher repeated her explanation in the previous meeting. The material of narrative text was familiar for the students because they already being introduced to this genre since they were in Junior High School. The students seemed already had good basic knowledge of narrative, so they were able to answer the teachers questions. The students pay attention to the teacher’s explanation. Some of them were also taking notes from the teacher’s explanation. Some girls in the second row, discussed about the material. The teacher explained about four-square writing technique. She also explained the application of this technique in writing. She gave an example of text which is made using four-square writing technique. The teacher gave the students a paper of blank sheet of Four-Square Writing Technique model. The students had to follow the guidelines given. In the first paragraph, they had to write introductory paragraph. In the second paragraph, they had to write the problem faced by the charachter(s). The resolution would be in the third paragraph and in the last paragraph, the students had to write the moral value of the story. After the teacher explained the task, the students started to make their own composition of narrative. Some students asked for more explanation to the teacher to make sure that they had already made the right composition. The teacher walked around the class to make sure that all of the students already understood the material and also understood how to use four-square writing technique in helping them to make a good composition of short story. THE STUDENTS’ TASK AFTER THE IMPLEMENTATION OF FOUR-SQUARE WRITING TECHNIQUE Content plays very important role in a composition because it takes the writer’s idea. There are four criteria in evaluating content. They are knowledgeable, substantive, through development of thesis and relevant to assign the topic (Jacob, 1981). The evaluation of content can be categorized into four levels. They are excellent to very good, good to average, fair to poor, and very poor. The students’ composition based on the content showed good result. There was no student who got “very poor” in terms of content. There are six criteria in evaluating organization of the composition. They are fluent expression, ideas clearly stated or supported, well organized, succinct, logical sequencing, and cohesive (Jacob, 1981). Jacob states that there are four levels to describe the writing ability in terms of organization. They are excellent to very good, good to average, fair to poor, and very poor. The students’ writing ability in terms of organization showed good result during the implementation of four-square writing technique. There was only a student got “poor” score in their organization of writing. In a compotition, vocabulary plays an important role that can measure whether the composition is understandable or not, since vocabulary is carrying the meaning and the ideas of the writer. Based on the ESL Composition Measurement by jacob (1981), there are four criteria in evaluating content. They are sophisticated range, effective word or idiom choice and usage, word form mastery, and appropriate register. It is also categorized into four levels, excellent to very good, good to average, fair to poor, and very poor. In terms of vocabulary, the students composition showed good result. The students used effective words. Some of them also showed off their vocabulary mastery by showing their ability in word choice which can make the students’ compositions understandable. Language also becomes one of the most important things in writing a composition. It is a sign which shows when the story take place. There are eight criteria to evaluate the student’s composition in terms of language used. They are effective complex constructions, few errors of agreement, tense, number, word order or function, articles, pronoun, preposition. The students’ composition based on the language used showed good result. There were only few minor error of agreements and preposition. Some of them had problem with tenses used in short story. However, those errors did not influence too much to the story. In writing, mechanics are , however, considered as important too. Mechanics show the intonation when the reader read the text. It also shows the writer emotions in the story. Jacob (1081) states that there are five criteria in evaluating a composition based on the mechanics. They are demonstrates mastery of conventions, few errors of spelling, punctuation, capitalization and paragraphing. In terms of mechanics, the students composition showed good result. Alomost all of the students did not have any problem with mechanics. They had already known when to put pull stop and coma, also another sign. DISCUSSION In terms of content, the result showed that the students were able to make good composition of short story. Most of the students were able to deliver their ideas through the composition they made. There was only one student who got “poor” level, while there were 8 students who got “very good” level. The result of the students’ task revealed that the students’ writing ability showed good result based on their writing organization. There were 2 students got “poor” score in terms of organization and there were 4 students considered as “very good”. The students. who got “fair to poor” level, failed to explore enough details to develop their composition and their stories went around the bus. The students’ task showed good result in terms of vocabulary. The students were able to show their mastery of vocabulary by using various word choice. There is only one student who got “poor” level and there was also one of the students who got “very good” level. In terms of language, the students’ task showed good result. Altough there still 3 students who got “poor” level. the problem was actually tense used in the short story. The students combined both present and past tense in their story, which actually should be in form of past tense. The students did not find any difficulties in terms of mechanics. It was proven by the result of their composition. There was no student got “poor” level in mechanics analysis. Minor errors as capitalization and punctuation were the most common errors done by the students. CONCLUSION The implementation of the first and second meeting were showed good result. All of the students pay attention to the teacher and actively asked some questions related to the material. It showed that the teacher had already succeed in implementing Four-Square Writing Technique in teaching narrative writing of Short Story to the Tenth Grader of SMA Muhammadiyah 2 Surabaya. The students compotition showed good result in terms of content, organization, vocabolary, language used and mechanics based on the ESL Composition Measurement written by Jacob (1981). It showed that the students can apply the Four-Square Writing Technique quite well. REFERENCES Abbot, G., et. al. 1981. The Teaching of English as an International Language to Practical Guide. Great Britain: William Collins Sons Co.Ltd. Anderson, Mark and Kathy Anderson.1997. Text Types in English 2. South Yarra: Mac Millian Education Australia Pty Ltd A Scott, Wendy and Ytreberg, Lisbeth H.1990.Teaching English to Children. USA : Longman Inc Eltis, K.J. 1990. A Genre Based Approach to Teaching Writing Years 3. Sydney: Common Ground Fitria, Ayu. 2011. The Implementation of Spider Map Strategy to Teach Writing Descriptive Text to The Seventh Grade of SMPN 2 Krian Sidoarjo.Surabaya:State University of Surabaya Gould, Judith S. & Evan Jay. 1999. Four Square Writing Technique. Teaching & Learning Company: Carthage, IL. Harmer, Jeremy.2001.The Practice of English Language Teaching 3rd Edition. England: Person Educational Limited Langan, J. (2001). English Skills. New York, The McGraw Hill Companies, Inc. Nunan, David.1991.Language Teaching Techniqueology: A Text Book for Teachers.Newyork:Pretice Hall International (UK) Ltd. Nunan, David.2003.Practical English Language Teaching. New York : McGraw-Hill Riafinah, Umu. 2011.Mind Mapping as an Alternative Strategy to Teach Speaking Narrative Text to The Eight Grade Students of SMP Zainuddin Sidoarjo. Surabaya:State University of Surabaya